1993
DOI: 10.1007/bf00169160
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endothelial derived relaxing factor (EDRF) aggravates ischemic acute renal failure in anesthetized rats

Abstract: The relative importance of endothelial derived relaxing factor (EDRF)/nitric oxide (NO) in maintaining kidney function in normal condition and in acute renal failure (ARF) were evaluated in inactin anesthetized rats. ARF was induced by unilateral occlusion of the left renal artery (40 min) followed by reperfusion, with the contralateral kidney serving as normal control. This protocol resulted in marked reductions in renal plasma flow (RPF), glomerular filtration rate (GFR) and increases in fractional sodium ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
3

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 23 publications
2
31
0
3
Order By: Relevance
“…Several studies have demonstrated that endogenous or exogenous NO protects the kidney against ischemia/reperfusion injury (Chintala et al, 1993;Schramm et al, 1994;Linas et al, 1997). Most recently, we noted that both exogenous and endogenous NO have protective effects Fig.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Several studies have demonstrated that endogenous or exogenous NO protects the kidney against ischemia/reperfusion injury (Chintala et al, 1993;Schramm et al, 1994;Linas et al, 1997). Most recently, we noted that both exogenous and endogenous NO have protective effects Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, the inhibition of NO synthase (NOS) was seen to aggravate the postischemic ARF (Chintala et al, 1993), thereby suggesting the renoprotective role of endogenous NO in this disease. On the other hand, NO may be deleterious because of its reactivity with oxygen free radicals produced during reperfusion of the ischemic kidney to yield toxic products, such as peroxynitrates (Pryor and Squadrito, 1995).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of NO donors such as sodium nitroprusside, molsidomine, and FK-409 is beneficial in renal I/R injury (19,24,31,42). L-Arginine supplementation and NOS inhibitors have shown varying results (4,24,37,41,43,50). Inhibition of iNOS using antisense oligonucleotides is beneficial in renal I/R injury (37).…”
Section: Discussionmentioning
confidence: 99%
“…7) In contrast, in vivo studies have shown a beneficial effect of NO in ischemic ARF models: the inhibition of NO production with a non-selective NOS inhibitor significantly deteriorated renal function of ischemic ARF rats, whereas the NOS inhibitor-induced renal dysfunction was abolished by L-arginine. 8) We have also found that renal dysfunction in ischemic ARF rats is markedly attenuated by pre-ischemic treatment with (Ϯ)-(E)-4-ethyl-2-[(E)-hydroxyimino]-5-nitro-3-hexenamide (FK409), a NO donor, thereby suggesting that pre-ischemic treatment with the NO donor has a protective effect against renal injury in vivo models of ischemic ARF 9) ; however, it is unclear whether post-ischemic treatment with a NO donor could suppress the ischemia/reperfusion-induced renal dysfunction.…”
mentioning
confidence: 99%